The Need for the Development of PjBL-Based Social Studies E-LKPD for Elementary School Students - Usman, Herlina; Suntari, Yustia; Wulandari, Yosi (Universitas Pendidikan Ganesha, 2024)
The critical thinking skills of elementary school students still need to be re-considered, especially in learning Social Sciences (IPS). One way to improve critical thinking skills is by using teaching materials in the form of Electronic Student Worksheets (E-LKPD) for Social Studies. This study aims to analyze the needs in developing project-based (PjBL) IPS E-LKPD, the products developed are expected to be able to improve the critical thinking skills of elementary school students. The study was conducted in an elementary school in East Jakarta with 34 students as research subjects. This study uses the ADDIE model development research type. However, in this study the researcher only conducted the analysis stage to determine the analysis of student and teacher needs so that the development of the IPS E-LKPD product is in accordance with field needs. The data collection techniques used were interviews and filling out questionnaires with descriptive analysis techniques. The data were analyzed using descriptive analysis techniques to analyze the social learning process and analyze student characteristics. The results of the analysis showed that the teaching materials in the form of LKPD developed by teachers still had several shortcomings. Therefore, schools really need the right E-LKPD for learning, especially PjBL-based IPS E-LKPD in accordance with the Merdeka Curriculum. The latest information in this study has implications as reference material or analysis information for further research in developing PjBL-based IPS E-LKPD products. Thus, the products developed are in accordance with field needs and can be an alternative solution to existing problems.